2013
DOI: 10.2105/ajph.2011.300600
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Provider Recommendation, Human Papillomavirus Vaccination, and Race/Ethnicity in the US National Immunization Survey

Abstract: Provider recommendations were strongly associated with HPV vaccination. Racial/ethnic minorities and non-Hispanic Whites were equally likely to obtain an HPV vaccine after receiving a recommendation. Vaccine education efforts should target health care providers to increase recommendations, particularly among racial/ethnic minority populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
201
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(223 citation statements)
references
References 22 publications
17
201
5
Order By: Relevance
“…10 All but one study examining patients' race/ethnicity suggested disparities in provider communication with parents of African American and Hispanic adolescents less often discussing HPV vaccine with a provider or receiving HPV recommendations than parents of non-Hispanic White adolescents. 7,64,[66][67][68][69][70] This pattern of findings is concerning given that both quantitative and qualitative studies suggested that provider recommendations were especially influential among parents from racial/ethnic minority backgrounds. 19,69,[71][72][73] Providers more often recommended HPV vaccination for patients they perceived to be at higher risk for HPV infection.…”
Section: Preferences In Communication Source By Provider Typementioning
confidence: 99%
See 1 more Smart Citation
“…10 All but one study examining patients' race/ethnicity suggested disparities in provider communication with parents of African American and Hispanic adolescents less often discussing HPV vaccine with a provider or receiving HPV recommendations than parents of non-Hispanic White adolescents. 7,64,[66][67][68][69][70] This pattern of findings is concerning given that both quantitative and qualitative studies suggested that provider recommendations were especially influential among parents from racial/ethnic minority backgrounds. 19,69,[71][72][73] Providers more often recommended HPV vaccination for patients they perceived to be at higher risk for HPV infection.…”
Section: Preferences In Communication Source By Provider Typementioning
confidence: 99%
“…7,64,[66][67][68][69][70] This pattern of findings is concerning given that both quantitative and qualitative studies suggested that provider recommendations were especially influential among parents from racial/ethnic minority backgrounds. 19,69,[71][72][73] Providers more often recommended HPV vaccination for patients they perceived to be at higher risk for HPV infection. Studies found that providers prioritized HPV vaccination for subpopulations including sexually active adolescents, males who might have same sex partners, and adolescents of lower socioeconomic status.…”
Section: Preferences In Communication Source By Provider Typementioning
confidence: 99%
“…The possibility that 35% of girls were not recommended HPV vaccine by their provider is concerning given the strong association between clinician recommendation and receipt of HPV vaccines. [14][15][16][17][18][19] It is also possible some parents do not perceive their child's provider as recommending HPV vaccination due to the way the recommendation is presented. Studies show clinicians may discuss HPV vaccines separately from other vaccines for adolescents, present HPV vaccine as optional while other recommended vaccines are described as necessary, or fail to provide parents with adequate information about HPV vaccines.…”
Section: ããmentioning
confidence: 99%
“…8,9,[11][12][13][14][15] Parents reporting a clinician recommendation for HPV vaccine are more likely to report intentions to vaccinate their children 13,15 and teens whose parents received a clinician recommendation are more likely to receive HPV vaccine. [14][15][16][17][18][19][20] Although HPV vaccination is recommended for adolescents 11-12 y old, clinicians may give stronger recommendations to older teens due to beliefs that HPV vaccination requires discussion of sexuality that is inapplicable to younger adolescents or may offend the preteen's parents. 9,12,[21][22][23][24] Similarly, parents report -and clinicians perceive -greater parental acceptability of HPV vaccine for older teens.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 For example, because few providers were equipped to make strong endorsements of human papilloma virus vaccine when it was first introduced in the US, uptake of the vaccine suffered. 26 In a large country like India, provider education is not an easy feat, but the existing infrastructure for polio eradication campaigns can be leveraged to accomplish this. Since 46% of the children we studied received most of their immunizations from the private sector, it is important to educate private practitioners as well.…”
Section: Applying These Motivators To the United Statesmentioning
confidence: 99%